1982
DOI: 10.1007/bf00541245
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 activity in the synovial fluid of patients with rheumatoid arthritis

Abstract: The synovial fluids (SF) of patients with rheumatoid arthritis (RA) were investigated for their effects on thymocytes of C3H/HeJ mice. Of the 20 SF tested, 17 (85%) showed an augmentation of the phytohaemagglutinin (PHA) induced thymocyte stimulation. Out of 16 SF of patients with osteoarthrosis, such an activity was detected in only one (6.25%). Further characterisation of the amplification factor revealed that (1) the SF of RA patients augmented both the PHA and the Concanavalin A response of the thymocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
94
1
4

Year Published

1983
1983
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(108 citation statements)
references
References 15 publications
9
94
1
4
Order By: Relevance
“…Our results differ from those of Fontana et a1 (24) and from those of other investigators studying lymphocyte stimulating activities in inflamed joints (6)(7)(8)26) in that the others have found the activity only in fluids from rheumatoid joints and not from osteoarthritic joints. There are at least two explanations for the discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results differ from those of Fontana et a1 (24) and from those of other investigators studying lymphocyte stimulating activities in inflamed joints (6)(7)(8)26) in that the others have found the activity only in fluids from rheumatoid joints and not from osteoarthritic joints. There are at least two explanations for the discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…This may correlate with the higher levels of MCAF in RA SF. Various cytokines, including IL-1, IL-6, IL-8, and GM-CSF, have been also shown to be present at higher levels in RA SF than in OA SF (20,22,23,25). We have also shown that freshly isolated SF cells and synovial tissue from patients with RA express MCAF mRNA.…”
Section: Discussionmentioning
confidence: 55%
“…To quantify the amplified transcripts, PCR was conducted by incorporation at 14-34 cycles using cDNA samples from FLS. The amounts of amplified products of MCAF and &m were exponential at [14][15][16][17][18][19][20][21][22][23][24][25][26] cycles and then decreased slowly (data not shown); PCR amplification of cDNA for MCAF and &m was consequently carried out for 20 cycles in this study. As shown in Figure 5 , 188 bp of MCAF transcripts were detected in FLS incubated with the medium alone.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that IL-1 (a potent inducer of IL-6 synthesis) is found in high concentrations in the synovial fluid of patients with inflammatory joint diseases [31,32]. Chondrocytes respond to IL-1 by the release of hydrolases [33] and in turn an increase of proteoglycan degradation [13,14].…”
Section: Resultsmentioning
confidence: 99%